Recognizing the Benefits of Pre-/Probiotics in Metabolic Syndrome and Type 2 Diabetes Mellitus Considering the Influence of Akkermansia muciniphila as a Key Gut Bacterium - Raluca Anca Corb Aron; Areha Abid; Cosmin Mihai Vesa; Aurelia Cristina Nechifor; Tapan Behl; Timea Claudia Ghitea; Mihai Alexandru Munteanu; Ovidiu Fratila; Felicia Liana Andronie-Cioara; Mirela Marioara Toma; Simona Bungau (Microorganisms, 2021)
Metabolic syndrome (MetS) and type 2 diabetes mellitus (T2DM) are diseases that can be influenced by the structure of gut microbiota, whose improvement is often neglected in metabolic pathology. This review highlights the following main aspects: the relationship between probiotics/gut microbes with the pathogenesis of MetS, the particular positive roles of Akkermansia muciniphila supplementation in the onset of MetS, and the interaction between dietary polyphenols (prebiotics) with gut microbiota. Therefore, an extensive and in-depth analysis of the often-neglected correlation between gut microbiota and chronic metabolic diseases was conducted, considering that this topic continues to fascinate and stimulate researchers through the discovery of novel strains and their beneficial properties.